CP-058 Identification of key areas for antimicrobial stewardship strategies in a large university teaching hospital: A point prevalence study. (14th February 2016) - Past, E; Porsche, U; Kern, JM; Stalzer, P; Rolke, J; Brunauer, A; Hell, M; Lechner, A
Abstract : Background: Antimicrobial stewardship teams (AMT) are key to safeguard the efficacy of antimicrobial drugs, and to minimise toxicity, emergence of resistance and costs. Prospective audit and feedback interventions are antimicrobial stewardship strategies (ASS) with a high potential for educational opportunities, where areas for improvement can be objectively identified. Purpose: The aim of this study was to determine the prevalence of inappropriate antimicrobial prescribing in a 1000 bed university teaching hospital and to identify specific topics to be targeted by ASS. Material and methods: A point prevalence study (PPS) was conducted on an index day in March 2015 by the hospital´s multidisciplinary AMT, using a paper based audit tool. All inpatients aged >18 years prescribed at least one antimicrobial agent were included. Data regarding patient demographics, antimicrobial prescriptions, indications and microbiological results were extracted from the paper based medical records. The appropriateness of antimicrobial use was assessed by the AMT against their own local guidelines. General feedback for the hospital and detailed evaluation for each department were assembled. Results: Among 779 included inpatients, 208 (26.7%) received one or more antimicrobial agents. Antimicrobial therapy was deemed inappropriate in 71 patients (34.1%), with the wrong choice of antibiotic as the most common reason (n = 45, 63.4%). Dosing errors were under doses in patients with renal insufficiency (n = 16, 22.5%). Inappropriate prescribing was associated with the use of specific antibiotics: co-amoxiclav (dosing), moxifloxacin (choice) and meropenem (choice and dosing), and specific pathologies: presumed diagnoses of sepsis, and urinary tract and respiratory infections. The indication for an antimicrobial agent was not documented in 51 patients (24.5%). The use of parenteral antimicrobials was high (n = 211, 76.2%). A switch from parenteral to oral formulations for the current infection was rarely performed (n = 10, 3.6%). Conclusion: The PPS on antimicrobial prescribing was a structured approach to identify necessary ASS in our hospital. Plans for 2016 include guidance and restrictions on moxifloxacin and meropenem; dosing in renal insufficiency and renal replacement therapies; updated guidelines on sepsis, and urinary tract and respiratory infections. Educational activities will embrace the dissemination of the audit feedback via academic detailing and lectures. A re-audit of the specified topics will follow. No conflict of interest.